2010
DOI: 10.1080/00048623.2010.10721432
|View full text |Cite
|
Sign up to set email alerts
|

Cross Country Comparison of Scholarly E-Reading Patterns in Australia, Finland, and the United States

Abstract: Surveys of academic staff in Australia, Finland, and the United States from 2004-2007 reveal readingpatterns of e-articles by academics that can be used to measure the purpose and value of e-reading and to demonstrate the value of library-provided electronic journal collections. Results can also be used to compare differences across subject discipline, age, and national boundaries, and how the decisions that libraries make influence reading patterns. The surveys used a variation of the critical incident techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 15 publications
5
36
1
1
Order By: Relevance
“…8,9 This convenience of e-access anywhere and anytime led to the situation where, by the mid-2000s, the majority of journal article readings were accessed by faculty electronically, mostly from having access through their library, and over half were read from an electronic version away from a physical library. 22 By 2011 in the United Kingdom, 94% of library article readings by faculty members in research universities were obtained through e-journal collections.…”
Section: Background and Research Questionsmentioning
confidence: 99%
See 2 more Smart Citations
“…8,9 This convenience of e-access anywhere and anytime led to the situation where, by the mid-2000s, the majority of journal article readings were accessed by faculty electronically, mostly from having access through their library, and over half were read from an electronic version away from a physical library. 22 By 2011 in the United Kingdom, 94% of library article readings by faculty members in research universities were obtained through e-journal collections.…”
Section: Background and Research Questionsmentioning
confidence: 99%
“…[11][12][13][14][15] Increasing availability of electronic articles, including backfiles, through libraries has been responsible for the largest percentage of the increase of e-article readings in the United States and elsewhere. 8,9 Therefore, libraries and publishers are both reacting to user preferences and driving changes in behaviour by changing to e-formats. Other studies also show the impact of electronic access and e-journals on changes to reading patterns.…”
Section: Background and Research Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Surveys from 2004 to 2007 of academics in the United States, Finland and Australia revealed that in the United States and Finland, faculty who published more also read more. 17 A recent study in the UK points in a similar direction: universities with more downloads of electronic articles had higher faculty publication rates. 18 A study at five US universities showed that faculty who publish more or who have won awards read more articles on average than their less productive colleagues.…”
Section: Value Of E-journalsmentioning
confidence: 71%
“…Many paths may lead to an article being found and read (Tenopir, Wilson, Vakkari, Talja, & King, 2010). These include keyword searching, citation chaining and journal browsing.…”
Section: Introductionmentioning
confidence: 99%